Analysis of the Impact of Credit Risk on the Financial Performance of the Financing Industry: A Comparative Study of the Period Before, During, and After the Covid-19 Pandemic (2017–2024) - Loblobly, Immanuel Simon; Djohanputro, Bramantyo; Rajagukguk, Wilson (Universitas KH. Abdul Chalim Mojokerto, 2026)
This study aims to analyze the impact of credit risk on the financial performance of the financing industry in Indonesia using a comparative study approach across the periods before the Covid-19 pandemic (2017–2019), during the pandemic (2020–2021), and after the pandemic (2022–2024). The data used are aggregated secondary industry data sourced from financing institution statistical reports published by the Financial Services Authority (OJK). Credit risk is proxied by the Non-Performing Financing (NPF) ratio, while financial performance is measured using Return on Assets (ROA). The analytical method employed is linear regression with dummy variables and interaction terms to capture differences in impact across crisis periods. The results show that credit risk has a negative and significant effect on the financial performance of the financing industry. In addition, the Covid-19 pandemic is proven to have strengthened the negative impact of credit risk on industry profitability, while the post-pandemic period indicates signs of performance recovery. These findings underscore the importance of adaptive credit risk management and the role of regulatory policies in maintaining the stability of the financing industry during periods of crisis and economic recovery.